Biohybrid Janus Motors Driven by Escherichia coli. Issue 2 (19th November 2015) - Stanton, Morgan M.; Simmchen, Juliane; Ma, Xing; Miguel‐López, Albert; Sánchez, Samuel
Abstract : There has been a significant interest in the development of microswimmers for medical drug and cargo delivery, but the majority of current micromotors rely on toxic fuel sources and materials in their design making them irrelevant for biomedical applications. Bacteria represent an excellent motor alternative, as they are powered using their surrounding biological fluids. For a motile, biohybrid swimmer, Escherichia coli ( E. coli ) are integrated onto metal capped, polystyrene (PS) Janus particles. Fabrication of the biohybrid is rapid and simple for a microswimmer capable of magnetic guidance and ferrying an anticancer agent. Cell adhesion is regulated as E. coli adheres only to the particle's metal caps allowing the PS surface to be utilized for drug attachment, creating a multifunctional system. E. coli adhesion is investigated on multiple metal caps (Pt, Fe, Ti, or Au) and displays a strong preference to attach to Pt surfaces over other metals. Surface hydrophobicity and surface charge are examined to interpret the cell specific adhesion on the Janus particles. The dual capability of the biohybrid to have guided cell adhesion and localized drug attachment allows the swimmer to have multiple applications for biomedical microswimmers, future bacteria‐interface systems, and micro‐biorobots. Abstract : Motile biohybrid swimmers are fabricated by integrating Escherichia coli onto metal capped, polystyrene (PS) Janus particles. Cell adhesion is regulated as E. coli adheres only to the particle's metal caps allowing the PS surface to be utilized for drug attachment, creating a multifunctional system. E. coli demonstrate the ability to carry multiple cargo loads, while maintaining high cell viability and proliferation.